2007
DOI: 10.1111/j.1530-0277.2007.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

fMRI BOLD Response to the Eyes Task in Offspring From Multiplex Alcohol Dependence Families

Abstract: Offspring from multiplex families for AD may manifest one aspect of their genetic susceptibility by having a diminished BOLD response in brain regions associated with performance of ToM tasks. These results suggest that those at risk for developing AD may have reduced ability to empathize with others' state of mind, possibly resulting in diminished social skill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 34 publications
6
39
1
Order By: Relevance
“…This pattern of activation has also been found amongst young people with high risk of alcoholism (i.e. from families with a history of alcohol dependence) (14) (15). This supports the idea that non-verbal language processing difficulties might partly precede the development of an addiction.…”
supporting
confidence: 76%
“…This pattern of activation has also been found amongst young people with high risk of alcoholism (i.e. from families with a history of alcohol dependence) (14) (15). This supports the idea that non-verbal language processing difficulties might partly precede the development of an addiction.…”
supporting
confidence: 76%
“…Consistent with previous data from our sample, the primary cognitive risks appear to be in the intelligence (Noll et al, 1992;Poon et al, 2000;Puttler et al, 1998) and executive function domains (Nigg et al, 2004). As found by Hill et al (2007), our large sample of high-risk adolescents/young adults from alcohol-dependent families was not different in RMET performance in comparison with controls. At the same time, based on the brain-behavior interaction fi ndings reported by Hill et al (2007), the unimpaired behavioral performance might be achieved through different processing strategies.…”
Section: Discussionsupporting
confidence: 92%
“…As found by Hill et al (2007), our large sample of high-risk adolescents/young adults from alcohol-dependent families was not different in RMET performance in comparison with controls. At the same time, based on the brain-behavior interaction fi ndings reported by Hill et al (2007), the unimpaired behavioral performance might be achieved through different processing strategies. Additional or alternative brain networks might be involved in the processing of social stimuli in children of alcoholics compared with healthy controls, giving enough resources to perform the task properly.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Findings from our lab concerning social cognition suggest that the ISA network may have relevance to risk for developing an AUD or related SUD. In an fMRI study using the Eyes Task which measures an individual’s ability to read the other person’s emotional state through facial expressions, we found that adolescent/young adult high-risk individuals had decreased BOLD activation in regions showing activation in controls [39]. Also, from a recent analysis of young adult offspring from families selected through women with alcohol dependence we find whole brain reduction of gray matter in multiple brain regions but particularly in regions having to do with facial processing (insula, fusiform cortex), regions that also held up under further analysis using ROI measures [Hill et al, Unpublished].…”
Section: Morphological Characteristics Of High-risk Offspringmentioning
confidence: 99%